Does anyone know what the book is doing in these step? I thought we would have substituted the two factors we just solved for into the 3rd equation but they’ve completly lost me on this step.
"Substituting this expression for the risk-free rate into the equation for E(Rk), we find, after simplication, that x1 = 0.04 - x2, Using x1 = 0.04 - x2, to eliminate x1, in the equation for E(Rj),
10 = Rf + 0.5x
Using x1, = 0.04 - x2 to eliminate x1, in the equation for E(Rj),
.058 = Rf - 0.2x"
Aren’t they saying we substitue x1 (calculated above as .04 - x2) into 0.11 = Rf + 1.3x1 + 1.1? Where is .058 = Rf - 0.2x coming from?!